Parameters of Reunification Therapy and Predictors of Treatment Success in High Conflict Divorce Cases: A Survey of Mental Health Professionals. Issue 8 (16th November 2020) - Baker, Amy J. L.; Murray, Colleen; Adkins, Kevin
ABSTRACT: One hundred and twenty licensed mental health professionals were surveyed about their work conducting court-ordered reunification therapy with moderate to severe cases of children's rejection of a parent. Four issues were examined in particular: assessment/screening of alienation VS. estrangement, development of treatment goals, definition and measurement of treatment success, and barriers to successful treatment. Predictors of successful treatment were also examined. Results indicate that how success was defined, whether joint sessions are offered, number of barriers, and percent of cases perceived to be hybrids all predicted percent of successful cases. Findings offer many opportunities for refining and enhancing this very challenging work.